2019
DOI: 10.21791/ijems.2019.1.37.
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TIG Reheating on Duplex Stainless Steel Weld Microstructure

Abstract: Duplex stainless steels (DSS) gaining their excellent mechanical properties and corrosion resistance due to their austenitic-ferritic microstructure, ideally in the same amount. However, to keep this ideal phase ratio during arc welding is very difficult. Generally, the arc welding processes will result in more ferritic microstructure in the weld metal and in the heat affected zone, due to the rapid cooling. The ferritic microstructure can cause chromiumnitride precipitation, because the nitrogen solubility in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A certain amount of work, in the field of welding duplex stainless steels, has devoted constructive research in the microstructure evolution after reheating the fusion region [25][26][27] and the heat affect zone (HAZ) [19,28,29]. It was found that secondary austenite generated both in the reheating fusion region and the reheating HAZ in the form of intragranular γ 2 and intergranular γ 2 .…”
Section: Secondary Austenite Transformationmentioning
confidence: 99%
“…A certain amount of work, in the field of welding duplex stainless steels, has devoted constructive research in the microstructure evolution after reheating the fusion region [25][26][27] and the heat affect zone (HAZ) [19,28,29]. It was found that secondary austenite generated both in the reheating fusion region and the reheating HAZ in the form of intragranular γ 2 and intergranular γ 2 .…”
Section: Secondary Austenite Transformationmentioning
confidence: 99%
“…It has been reported by Chenhua, [15] Zhang, [4] and Ramirez [16] that the selective corrosion of γ 2 in the HAZ resulted from the lower Cr and Mo content of the γ 2 compared with the ferrite and γ 1 . Our research team [17][18][19] and other researchers [9,20,21] previously carried out lots of studies on how to promote more austenite formation and inhibit Cr 2 N and γ 2 precipitation in the HAZ of DSS welded joint by changing welding methods, optimizing welding DOI: 10.1002/srin.202300460…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by Chenhua, [ 15 ] Zhang, [ 4 ] and Ramirez [ 16 ] that the selective corrosion of γ 2 in the HAZ resulted from the lower Cr and Mo content of the γ 2 compared with the ferrite and γ 1 . Our research team [ 17–19 ] and other researchers [ 9,20,21 ] previously carried out lots of studies on how to promote more austenite formation and inhibit Cr 2 N and γ 2 precipitation in the HAZ of DSS welded joint by changing welding methods, optimizing welding process, and alloying treatment. The latest research [ 22–24 ] showed that the austenite content in the HAZ can be increased to above 30% by using hybrid welding technique, N 2 addition into shielding gas, or postweld heat treatment.…”
Section: Introductionmentioning
confidence: 99%